Using electronic monitoring with female offenders in Thailand - SASIPHATTRA SIRIWATO; SUPPAKORN POONYARITH (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: This paper aims to identify the benefits and drawbacks of using EM as an alternative to incarceration for female offenders who are either (1) pregnant, (2) breastfeeding, (3) mothers with children in prison, or (4) women with dependent children.Method: This investigation relied on qualitative strategies. In-depth interviews were conducted with women who had used the EM as an alternative to incarceration to learn more about the program’s benefits and drawbacks. Ten female offenders were interviewed about their experiences with EM.Findings: According to this study, most people experience high levels of stress and anxiety during the first week of EM treatment. However, they are in better mental and physical health after that time and report feeling better. The results also showed that female offenders felt better after using the EM for a while. Each period has a higher total point value, as can be seen. This indicates that when using EM as an alternative to incarceration, all participants felt better and experienced less stress.Implications/Novel Contribution: Tiny and practical, the GPS device tracks your every move. However, today it is only valid in mainland Europe. Since other developing countries use more modern technology and successfully use the EM as an alternative imprisonment, it should not be difficult for the Thai government to solve the problem of the EM’s outdated technology.